PENGARUH TOTAL PADATAN TERSUSPENSI TERHADAP BIODIVERSITAS MAKROZOOBENTOS DI PANTAI TELUKAWUR KABUPATEN JEPARA - Arif Mustofa (Jurnal DISPROTEK, 2018)
The coastal waters of Telukawur Beach Jepara Regency is utilized by the surrounding community for various activities. Sediment transport passed on the rivers also community activities causes turbidity from suspended solids. This situation affects biodiversity especially macrozoobentos in these waters. This study aims to determine the total suspended solids and their effect on macrozoobenthos. The study used a pusposive method. It is used to measure total suspended solids as well as biodiversity analysis covering the index of diversity, diversity index, dominance index and relative diversity. The results showed the total suspended solids in Telukawur coastal waters of Jepara Regency ranged between 104.22 mg / l - 134.12 mg / l. The total suspended solids has a very strong effect (r = 0.934) on the abundance of macrozoobentos with a relative abundance range of 10.969% - 34.004%.